Evaluation of interfacial strength of multilayer thin films polymer by nanoindentation technique - Kenji INOUE; Farid TRIAWAN; Kazuaki INABA; Kikuo KISHIMOTO; Masashi NISHI; Michiyo SEKIYA; Kunihiko SEKIDO; Akihito SAITOH (Mechanical Engineering Journal, 2019)
Multilayer thin films polymer have been commonly used in a wide range of electronics applications, such as solar cells, photoconductors, semiconductors, and light-emitting diodes, in which failure due to delamination can occur. For evaluating and improving the quality of a multilayer thin-film product, the interfacial strength between its layers must be measured correctly and accurately. In this work, the interfacial strength of a multilayer thin-film polymer was quantified by measuring the interfacial energy release rate (interfacial fracture toughness), Gi , using the nanoindentation test technique. Three specimens of four-layer thin films were fabricated on a glass substrate. The top layer of each specimen was prepared with different thicknesses. The unloading curve technique introduced by Kozuki and Kishimoto (2010) was implemented to quantify the Gi of each specimen. Then, cross-sectional observation of the specimens was performed to confirm the layer thicknesses and to identify the delamination condition after the test. The measured Gi tended to increase as the range between the two unloading curves used to calculate the delamination energy widened. This phenomenon is believed to be caused by the plastic energy of the deformed films during the indentation process. Finally, an empirical method for eliminating the effect of the plastic energy on the measured Gi was proposed. Using this method, a pure Gi value can be effectively extracted; thus, the interfacial strength of multilayer thin-film polymers can be measured correctly and accurately.